2014
DOI: 10.1007/s40519-014-0168-6
|View full text |Cite
|
Sign up to set email alerts
|

Are Iranian obese women candidate for bariatric surgery different cognitively, emotionally and behaviorally from their normal weight counterparts?

Abstract: The findings showed that obese women candidates for bariatric surgery suffered from more cognitive, emotional and behavioral vulnerability compared to women with normal weight. Addressing these vulnerabilities among obese women could improve outcomes of weight loss surgeries and cognitive behavioral interventions so that weight regain is minimized and better outcomes are achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
7
0
2
Order By: Relevance
“…Also, the use of strategies to accept feelings and situations proved to be reduced in OB‐BED in comparison with CTRL . However, it should be noted that comparative analysis including all participants with obesity in the same group, independent of having BED or not, failed to detect differences in cognitive reappraisal , distraction and acceptance of emotions , relative to CTRL group.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Also, the use of strategies to accept feelings and situations proved to be reduced in OB‐BED in comparison with CTRL . However, it should be noted that comparative analysis including all participants with obesity in the same group, independent of having BED or not, failed to detect differences in cognitive reappraisal , distraction and acceptance of emotions , relative to CTRL group.…”
Section: Resultsmentioning
confidence: 87%
“…Eight studies were found with regards to ER, addressing the general difficulty in accessing functional strategies or the specific use of certain ER strategies, classified as adaptive (cognitive reappraisal, acceptance, distraction) or maladaptive (suppression of feelings, rumination). Data relating to general access to functional ER strategies indicated less ability both in OB (17) and OB-BED (49) relative to CTRL. With respect to specific adaptive strategies, studies reported a decreased use of cognitive reappraisal in OB-BED when compared with OB-N/BED (50,51) and CTRL (49,52) groups.…”
Section: Systematic Review Of Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…People with obesity also report less emotional awareness and more difficulties in understanding emotions (Bergmann et al, 2016;Rommel et al, 2012;Willem et al, 2019). Furthermore, they use more maladaptive emotion regulation strategies, such as emotion suppression, at the expense of adaptive ones, such as acceptance, cognitive reappraisal, or refocus on planning (Fereidouni et al, 2015;Willem et al, 2019;Zijlstra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…si mesmo e a aparência, e pode resultar em um ciclo vicioso em indivíduos obesos. Ter como alvo esses mecanismos emocionais, cognitivos e comportamentais, especialmente em pacientes que buscam a cirurgia bariátrica, pode prolongar a perda de peso pós-cirúrgica e melhorar sua qualidade de vida (FEREIDOUNI et al, 2014).…”
Section: Resultsunclassified